1995
DOI: 10.1111/j.1432-1033.1995.0050o.x
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Substitutions in the Yeast Pichia Stipitis Xylitol Dehydrogenase Coenzyme-Binding Domain Affect the Coenzyme Specificity

Abstract: Directed mutagenesis has been used to identify a set of amino acids in the Pichia stipitis xylitol dehydrogenase, encoded by the xylitol dehydrogenase gene XYL2, which is involved in specific NAD binding. Within the binding domain, a characteristic βαβ‐fold is centered around a glycine motif GXGXXG also containing conserved aspartate and lysine/arginine residues. The mutation D207→G and the double mutation D207→G and D210→G increased the apparent Km for NAD ninefold and decreased the xylitol dehydrogenase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…Comparison with Coenzyme Switching Studies for Oxidoreductases of the SDR and Other Families-Such a drastic change in coenzyme specificity by single mutation observed in the present study has not been reported yet for dehydrogenases of the SDR (37-39) and other families (17,19,40,41) in which systematic replacement of a set of amino acids in their ␤␣␤ folds is necessary to switch their coenzyme specificity. Although there has been no report on the mutation of the residue corresponding to Thr-38 of mouse lung CR in NADP(H)-dependent enzymes of the SDR family, the reverse-sense mutation, i.e.…”
Section: Fig 2 Effects Of Coenzymes On Thermal Inactivation Of Wt (supporting
confidence: 46%
“…Comparison with Coenzyme Switching Studies for Oxidoreductases of the SDR and Other Families-Such a drastic change in coenzyme specificity by single mutation observed in the present study has not been reported yet for dehydrogenases of the SDR (37-39) and other families (17,19,40,41) in which systematic replacement of a set of amino acids in their ␤␣␤ folds is necessary to switch their coenzyme specificity. Although there has been no report on the mutation of the residue corresponding to Thr-38 of mouse lung CR in NADP(H)-dependent enzymes of the SDR family, the reverse-sense mutation, i.e.…”
Section: Fig 2 Effects Of Coenzymes On Thermal Inactivation Of Wt (supporting
confidence: 46%
“…Similarly, attempts were made to increase the affinity of XDH for NADP + which resulted in improved ethanol production from xylose (Watanabe et al, 2007b;. The XYL2 gene has also been engineered by introduction of an NADP + recognition sequence from Thermoanaerobium brockii, resulting in an enzyme with equal K m values for NAD + and NADP + (Metzger and Hollenberg, 1995). The strain with the mutated XYL2 mediated growth on xylose when XYL1…”
Section: C H O +5adp+5pmentioning
confidence: 98%
“…This increased ethanol yield to 0AE4 g g )1 xylose and decreased xylitol production. In another attempt to recycle coenzyme by increasing the affinity of XDH for NADP + , an NADP + recognition sequence from Thermoanaerobium brockii was introduced into the XYL2 gene, resulting in equal apparent K m values for NAD + and NADP + (Metzger and Hollenberg 1995). Ehrensberger et al (2006) constructed a double mutant (D38S ⁄ M39R) of Gluconobacter oxydans XDH that was able to exclusively use NADP + , with no loss of activity.…”
mentioning
confidence: 99%